PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, SOLVABILITAS, PROFITABILITAS DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2013-2015) - Ayuna Feranica, 13.05.52.0077; Kartika, Andi (Students' Journal of Accounting and Banking, 2017)
The purpose of this study is to examine the influence of Firm Size, Liquidity, Solvency, Profitability, and size of Board of Commissioner to Corporate Social Resposibility Disclosure in Manufacturing Companies listed on the Indonesia Stock Exchange. The dependent variable is Corporate Social Resposibility Disclosure. Independent variable are Firm Size, Liquidity, Solvency, Profitability, and size of Board of Commissioner. The population in this study was all Manufacturing Company listed on the Indonesia Stock Exchange in 2013-2015. Samples were 249 manufacturing companies. This study used purposive sampling method.The analysis used in this reseacrh are multiple linear regression analysis.The results of the testing of hypotheses partial evaluation shows that there are significant influence on Firm Size, Liquidity, Profitability and size of Board of Commisioner while for Solvency not have significant influence to the Corporate Social Responsibility Disclosure.Keywords: Firm Size, Liquidity, Solvency, Proftitability, Size of Board of Commissioner, Corporate Social Resposibility Disclosure